Prognostic Value of Late Enhanced Cardiac Magnetic Resonance Imaging Derived Texture Features in Dilated Cardiomyopathy Patients With Severely Reduced Ejection Fractions - Shu, Shenglei; Wang, Cheng; Hong, Ziming; Zhou, Xiaoyue; Zhang, Tianjng; Peng, Qinmu; Wang, Jing; Zheng, Chuansheng (Frontiers in Cardiovascular Medicine, 2021)
Background: Late enhanced cardiac magnetic resonance (CMR) images of the left ventricular myocardium contain an enormous amount of information that could provide prognostic value beyond that of late gadolinium enhancements (LGEs). With computational post-processing and analysis, the heterogeneities and variations of myocardial signal intensities can be interpreted and measured as texture features. This study aimed to evaluate the value of texture features extracted from late enhanced CMR images of the myocardium to predict adverse outcomes in patients with dilated cardiomyopathy (DCM) and severe systolic dysfunction. Methods: This single-center study retrospectively enrolled DCM patients with severely reduced left ventricular ejection fractions (LVEFs<35%). Texture features were extracted from enhanced late scanning images, and the presence and extent of LGEs were also measured. Patients were followed for clinical endpoints composed of all-cause deaths and cardiac transplantation. Cox proportional hazard regression and Kaplan-Meier analyses were used to evaluate the prognostic value of texture features and conventional CMR parameters with event-free survival. Results: A total of 114 patients (37 women, median age 47.5 years old) with severely impaired systolic function (median LVEF, 14.0%) were followed for a median of 504.5 days. Twenty-nine patients experienced endpoint events, 12 died, and 17 underwent cardiac transplantations. Three texture features from a grey-level co-occurrence matrix (GLCM) (GLCM_contrast, GLCM_difference average and GLCM_difference entropy) showed good prognostic value for adverse events when analyzed using univariable Cox hazard ratio regression (p=0.007, p=0.011, p=0.007 retrospectively). When each of the three features was analyzed using a multivariable Cox regression model that included the clinical parameter (systolic blood pressure) and LGE extent, these features were independently associated with adverse outcomes. Conclusion: Texture features related LGE heterogeneities and variations (GLCM_contrast, GLCM_difference average and GLCM_difference entropy) are novel markers for risk stratification towards adverse events in DCM patients with severe systolic dysfunction.